Publicações artísticas : uma reflexão sobre publicações como arte pública em Vitória - Tonini, Juliana Colli (2015)
This work aims to study those publications that characterize as public exhibition spaces in the art field, based on an investigation over artistic proposals that deal with the propagation of the written language in an art context in Vitória – Espírito San